pep2pro: the high-throughput proteomics data processing, analysis, and visualization tool - Hirsch-Hoffmann, Matthias; Gruissem, Wilhelm; Baerenfaller, Katja (Frontiers in Plant Science, 2012)
The pep2pro database was built to support effective high-throughput proteome data analysis. Its database schema allows the coherent integration of search results from different database-dependent search algorithms and filtering of the data including control for unambiguous assignment of peptides to proteins. The capacity of the pep2pro database has been exploited in data analysis of various Arabidopsis proteome datasets. The diversity of the datasets and the associated scientific questions required thorough querying of the data. This was supported by the relational format structure of the data that links all information on the sample, spectrum, search database, and algorithm to peptide and protein identifications and their post-translational modifications. After publication of datasets they are made available on the pep2pro website at www.pep2pro.ethz.ch. Further, the pep2pro data analysis pipeline also handles data export do the PRIDE database (http://www.ebi.ac.uk/pride) and data retrieval by the MASCP Gator (http://gator.masc-proteomics.org/). The utility of pep2pro will continue to be used for analysis of additional datasets and as a data warehouse. The capacity of the pep2pro database for proteome data analysis has now also been made publicly available through the release of pep2pro4all, which consists of a database schema and a script that will populate the database with mass spectrometry data provided in mzIdentML format.